Electromagnetic shielding effectiveness performance of carbon fiber reinforced polymer (CFRP) composites with hematite and goethite in far-field - Erbas, Ugur; Kaykilarli, Cantekin; Eken, Taha Yasin; Kucukelyas, Burak; Tabakcioglu, Mehmet Baris (Pamukkale Univ, 2024)
Carbon fibers (CFs) are indispensable materials in our daily life. The excellent bearing capacity, remarkable dielectric property, ease of production, and corrosion resistance of CFRP composites distinguish them from all other options in addition to them, CFRPs may also shield from electromagnetic interference (EMI). In this study, two-layer CF reinforced epoxy composites reinforced with two different hematite (alpha- Fe2O3) and goethite (FeO(OH)) particle sizes of 50 nm and 45 mu m (325 mesh) were produced using the manual lay-up method. Then, far field electromagnetic shielding effectiveness (SE) with 700 MHz- 6000 MHz range were examined. The maximum shielding effectiveness was determined to be at 5200 MHz with 39.28 dB for 5 wt.% FeO(OH), at 4700 MHz with 38.38 dB for 10 wt.% Fe2O3(325 mesh), at 3800 MHz with 37.15 dB for 15 wt.% Fe2O3(50 nm).
Keywords: Carbon fibers; Far field; Electromagnetic shielding; carbon fiber reinforced polymer; Hematite; Goethite